Authority Sharing Between The Central and Regional Government in The Implementation of Pesantrens Law and Its Relevance to Hifdz Ad-Dîn Efforts - Wardhana, Allan Fatchan Gani (al-'adalah, 2023)
This study aims to examine the shift/sharing of authority between the Central and Regional Governments in the religious field, particularly regarding the implementation of Law Number 18 of 2019 concerning Pesantren. The Law provides a portion of authority to the Regional Government to facilitate Pesantrens in carrying out its functions as one of the centers for the development of Islamic religious knowledge. The Law also obliges the local Government to fund the Pesantrens through regional revenue and expenditure budgets by their authority and guided by statutory provisions. This study uses a normative juridical method. The results of this research conclude that the existence of the Pesantrens Law, on the one hand, shows that the Government has concern for efforts to maintain religion (Hifdz ad-Dîn); and, on the other hand, indicating that there has been a shift in authority from the Central to the Regional Government in governing of religion, particularly in terms of administering Pesantrens,